Effects of combined respiratory physiotherapy with high-flow nasal cannula and Venturi mask in spinal cord injury: a single-subject research study and literature review - Loredana Raciti; Gianfranco Raciti; Antonio Ammendolia; Sandro Maria Distefano; Rocco Salvatore Calabrò; Maria Pia Onesta; Gaetano Prosperini (European Journal of Case Reports in Internal Medicine)
Background: The level of spinal cord injury affects the severity of respiratory impairment and the alteration of respiratory pattern and gas exchanges. Lesions at the C3-C5 level (phrenic nerve nucleus) cause disruption of descending input with paralysis of the main inspiratory muscle, often requiring tracheostomy and prolonged mechanical ventilation. Oxygen therapy is essential to switch from ventilatory support to removal of the endotracheal tube to correct residual difficulties in oxygenation management. Case Presentation: A 58-year-old man had tracheostomy and tetraparesis as complication of tonsillectomy and adenoidectomy treatment for a history of obstructive sleep apnea. A respiratory rehabilitation program with protocol of oxygen therapy with high flow cannula alternated with a low-flow system by Venturi mask during daytime hours only was started. The patient was constantly monitored with capillary partial oxygen saturation to obtain adequate oxygenation (> 94%) and registered every 15 minutes in the clinical chart. There was gradual improvement of respiratory function. Oxygen by Venturi mask was gradually reduced due to improvement of partial pressure oxygen values. Over the course of days, the optimal results of respiratory parameters led to a gradual weaning from the Venturi mask until the complete discontinuation of the low-flow system during daytime and decreased of the high-flow fraction of inspired oxygen to the maximal tolerated level during nighttime. Conclusions: Implementing a combined protocol of nighttime oxygen with high flow cannula and daytime Venturi mask improves intensive motor training of patients by promoting the acquisition of ability to perform chair/bed transitions and to be able to achieve standing and begin gait training. More research is needed whether or noted to determine the role of this promising approach in patients with severe SCI and in other critically ill patients.